Educación superior y participación en el marco de la implementacion del presupuesto participativo en la comuna uno de Medellín (2010)
This text is the product of the developments of the project entitled: "Evaluation and Monitoring of the Social and Community Work of the Beneficiaries of the Participatory Budget Fund Aimed At Pursuing Higher Education Studies Belonging to Commune One, Medellin," in Partnership with the Secretariat of Education in the City of Medellin. It is aimed at going beyond an assessment of procedures, objectives, and outcomes, and in doing so; explore some dimensions of citizen participation in decision making and community benefits that this brings to the specific case of the Higher Education Project in the Commune One